Three new species of Oreophryne (Anura, Microhylidae) from Papua New Guinea - Fred Kraus (ZooKeys, 2013)
I describe three new species of the diverse microhylid frog genus Oreophryne from Papua New Guinea. Two of these occur in two isolated mountain ranges along the northern coast of Papua New Guinea; the third is from Rossel Island in the very southeasternmost part of the country. All three are the first Oreophryne known from these areas to have a cartilaginous connection between the procoracoid and scapula, a feature usually seen in species far to the west or from the central cordillera of New Guinea. Each of the new species also differs from the many other Papuan Oreophryne in a variety of other morphological, color-pattern, and call features. Advertisement-call data for Oreophryne species from the north-coast region suggest that they represent only two of the several call types seen in regions further south, consistent with the relatively recent derivation of these northern regions as accreted island-arc systems. The distinctively different, whinnying, call type of the new species from Rossel Island occurs among other Oreophryne from southeastern Papua New Guinea but has been unreported elsewhere, raising the possibility that it may characterize a clade endemic to that region.